THE EFFECT OF SOAKING PAPAYA (CARICA PAPAYA L.) JUICE ON WATER CONTENT AND AROMA OF LAMB - Ardian Ozzy Wianto; Lusia Risyani Padmaningdiah Mahagiani (Bantara Journal of Animal Science, 2022)
The study aims to determine the effect of the use of unripe papaya juice on the physical quality of lamb, namely water content and aroma. The material used in this study was two-year-old Jawarandu goat meat from the thigh topside as much as 300 grams. The observed parameters are water content and aroma.  The treatment tried was T0 : Meat soaked without unripe papaya juice, T1 : Meat soaked in unripe papaya juice concentration 6%, T2 : Meat soaked in unripe papaya juice concentration 8%, T3 : Meat soaked in unripe papaya juice concentration 10%. The results showed that soaking papaya juice with a concentration of 0%-10% had no noticeable effect on the moisture content and aroma of lamb. The conclusion of the study is that the use of unripe papaya essence can be used up to the level of 10% without affecting the moisture content and aroma of the lamb. Keywords: aroma, papaya, water content